2002
DOI: 10.1063/1.1527697
|View full text |Cite
|
Sign up to set email alerts
|

Atomic structure of steps and defects on the clean diamond (100)-2×1 surface studied using ultrahigh vacuum scanning tunneling microscopy

Abstract: We report ultrahigh vacuum scanning tunneling microscopy studies of the clean nonhydrogen-terminated diamond (100)-2×1 surface showing single- and double-layer steps that are rebonded. The main defects observed are single, multiple, and row dimer vacancies, and antiphase boundaries. Buckling of dimers is not observed, consistent with symmetric dimers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 8 publications
(7 reference statements)
0
7
1
Order By: Relevance
“…This is in contrast to the more uniform view of the dimer rows seen in the STM images on hydrogen-free CVD semiconducting diamond 21 or single-crystal insulating diamond. 20 In the latter STM study, a uniform one-dimensional density of states was observed due to the delocalization of the barrier resonances along the dimer rows.…”
contrasting
confidence: 49%
See 1 more Smart Citation
“…This is in contrast to the more uniform view of the dimer rows seen in the STM images on hydrogen-free CVD semiconducting diamond 21 or single-crystal insulating diamond. 20 In the latter STM study, a uniform one-dimensional density of states was observed due to the delocalization of the barrier resonances along the dimer rows.…”
contrasting
confidence: 49%
“…This is in contrast to high-resolution STM images of the hydrogenated diamond 6,15-18 and hydrogen-free diamond surfaces. [19][20][21] STM images of the hydrogenated diamond ͑100͒ surface could not separate the hydrogen atoms, which are clearly resolved in the NC-AFM image presented here. On the clean diamond ͑100͒ surface, individual C-C dimers could not be seen with the STM whereas they are clearly visible with the NC-AFM as demonstrated in this work.…”
mentioning
confidence: 71%
“…Both filled- (2 eV below fermi) and empty-state (2 eV above fermi) images were simulated for bare and adsorbed diamond(001) by nitrogen species and are visualized in Figure . At present, there is limited STM work on diamond yielding images of bare diamond (001) similar to Figure a′,a″. In the filled-state images (Figure , middle column), the carbon dimer rows of the diamond substrate are bright, as dominated by the π bonding state (Figure a′); the nitrogen species are visible because there are N states (Figure b′–d′) in the sampled energy window.…”
Section: Resultsmentioning
confidence: 99%
“…Atomically smooth C(100) surfaces can be prepared through the growth of homoepitaxial layers by chemical vapor deposition 51,52 . Upon thermal annealing, hydrogen desorption takes place and leads to the formation of clean C(100) 2 × 1 surfaces via surface reconstruction [53][54][55][56] . Figure 8 shows the variation of total energy during the process of wafer bonding between two clean C(100) 2 × 1 surfaces.…”
Section: Resultsmentioning
confidence: 99%